The Influence of Exchange Rate on Inflation in Indonesia (2003 – 2012) - Indirasari Cynthia Setyoparwati; Munawar Ismail (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study examines the effect of the exchange rate on inflation in Indonesia by using monthly data of the period of 2003-2012. In addition to entering the exchange rate as the main independent variable, this study also includes SBI rate and the money supply as a control variable. By applying multiple regression, this study confirmed that the exchange rate and interest rate SBI significantly affected inflation. Meanwhile, the money supply was not a significant variable influencing inflation. Keywords: Inflation, SBI Rate, Money Supply, Exchange Rate